Menurunkan Kecemasan dan Tekanan Darah pada Pasien Hipertensi dengan Kombinasi Relaksasi Otot Progresif dan Terapi Musik Binaural Beats. - Cahyono, Ibnu; Sentot Imam Suprapto; Joko Prasetyo (PT. Pubsains Nur Cendekia, 2024)
Hypertension, or high blood pressure, is a non-communicable disease that, if untreated, can lead to severe health issues and even death. Anxiety caused by health problems can contribute to elevated blood pressure at any age. This study analyzed the effects of combining Progressive Muscle Relaxation (PMR) with binaural beats music on anxiety and blood pressure in hypertensive patients. The research used a quasi-experimental design with pretest-posttest control groups and involved 44 hypertensive patients from the Sematu Jaya Health Center, selected through purposive sampling. The independent variable was the combination of PMR and binaural beats music, while the dependent variables were anxiety and blood pressure. Results from the Multivariate Analysis of Variance (MANOVA) showed significant effects on anxiety (p = 0.000, Eta² = 0.690), systolic blood pressure (p = 0.000, Eta² = 0.455), and diastolic blood pressure (p = 0.000, Eta² = 0.516). These findings indicate that the combination of PMR and binaural beats is effective in reducing both anxiety and blood pressure in hypertensive patients. This intervention is simple to implement and can be used as a nursing intervention to improve patient care in health centers.